2015
DOI: 10.1177/0019793915570873
|View full text |Cite
|
Sign up to set email alerts
|

Is There Less Discrimination in Occupations Where Recruitment Is Difficult?

Abstract: The authors empirically test the cross-sectional relationship between hiring discrimination and labor market tightness at the level of the occupation. To this end, they conduct a correspondence test in the youth labor market. In line with theoretical expectations, results show that, compared to natives, candidates with a foreign-sounding name are equally often invited to a job interview if they apply for occupations for which vacancies are difficult to fill; but, they have to send out twice as many application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
152
4
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(168 citation statements)
references
References 57 publications
8
152
4
4
Order By: Relevance
“…Correspondence experiments to test for hiring discrimination on such grounds as ethnicity, gender, beauty and sexual orientation have been extensively used and refined during the last decade [1,6,12,31,36]. Within these field experiments, pairs of fictitious written job applications are sent to real job openings.…”
Section: Measuring Unequal Treatment By a Correspondence Testmentioning
confidence: 99%
See 2 more Smart Citations
“…Correspondence experiments to test for hiring discrimination on such grounds as ethnicity, gender, beauty and sexual orientation have been extensively used and refined during the last decade [1,6,12,31,36]. Within these field experiments, pairs of fictitious written job applications are sent to real job openings.…”
Section: Measuring Unequal Treatment By a Correspondence Testmentioning
confidence: 99%
“…1 Given the costs associated with their unfavourable outcomes -costs at both the individual and the societal levels -it is not surprising that integrating the disabled into the labour market is a key ambition of many OECD countries [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a situation of shortage of labour, firms cannot 'afford' to discriminate against applicants with ethnic minority background (Midtbøen 2015a;Baert et al 2015). By contrast, when unemployment is high and firms can pick and choose among a series of qualified candidates, employers are more likely to hire applicants of majority backgrounds.…”
Section: The Economic Situation In the Destination Countrymentioning
confidence: 99%
“…Field experiments of employment discrimination have been conducted in countries like Germany (Kaas & Manger 2012), France (Duguet et al 2010), the Netherlands (Andriessen et al 2012), Belgium (Baert et al 2015), Switzerland (Fibbi, Lerch & Wanner 2006), Italy (Allasino et al 2004), Spain (de Prada, Actis & Pereda 1996, Greece (Drydakis 2012), Canada (Oreopoulos 2011), Australia (Booth, Leigh & Varganova 2012), United Stated (Bertrand & Mullainathan 2004;Pager, Western & Bonikowski 2009), Britain (Wood et al 2009), Sweden (Bursell 2014;Carlsson & Rooth 2007), Denmark (Hjarnø & Jensen 2008) and Norway (Midtbøen & Rogstad 2012b;Birkelund et al 2014), demonstrating the prevalence of racial and ethnic discrimination in a wide range of institutional contexts (see reviews in Pager 2007;Riach & Rich 2002;OECD 2013a). Results have varied across countries, but not a single study has concluded that discrimination is not a relevant factor in shaping access to employment for racial and ethnic minority groups.…”
Section: Critique Of the Ethnic Penalty Approach And The Role Of Discmentioning
confidence: 99%